Analisis Teori Kepemimpinan Genetik, Sosial dan Ekologis Pada Kajian Manajemen Pendidikan Islam - Eneng Siti Suherni; Anis Zohriah; Anis Fauzi (Departement of Mathematics Education, 2023)
Becoming a successful leader in leadership is certainly not easy, there are many problems that arise when we become a leader, one of the support for one’s leadership success is by studying leadership theory. In writing this article using library research which aims to collect data (quantitative) and information related to leadership theory. The data sources used are related to books or journals. Leadership theory is the origin of the emergence of a person’s ability to run, organize, process and provide success to an organization or institution he leads. Furthermore there are three theories of leadership, namely: genetic, social and ecological. Genetic leadership theory, namely abilities / talent that are born from birth, social skills theory namely abilities/ talents that are obtained through a learning process and ecological leadership namely abilities that have been obtained from birth and strengthened through the learning process. Regarding the leadership theory, the authors argue that a person’s ability to lead would be even better and very wise if it was accompanied by a learning process because by processing and continuing to learn, of course good result will accompany every policy.